Stock Market Participation Awareness among University Students in Nepal - Lama, Anil Kumar; Karki, Gyanendra; Neupane, Sangam (NPRC Journal of Multidisciplinary Research, 2024)
Financial Literacy amongst students is very important aspects. Therefore, as part of Financial Literacy, a study was conducted amongst 120 students of various colleges and fields to explore the awareness level of stock market investments in the Kathmandu valley. With a growing number of young investors entering the financial market, this research seeks to understand the factors that influence students' engagement with the stock market, particularly in a developing economy like Nepal. The study employs both qualitative and quantitative methodologies, including surveys distributed to students across various colleges in Nepal. Findings reveal that while there is moderate awareness about the stock market among students, actual participation remains limited. The main barriers include a lack of financial literacy, limited disposable income, and perceived risks associated with stock investments. Furthermore, cultural attitudes towards saving and investing also play a significant role in shaping students' engagement with the stock market. The research underscores the importance of integrating financial education from the school level itself to equip students with the knowledge and confidence to participate in the stock market. This study contributes to the existing literature on financial literacy and investment behaviors, offering insights into the unique challenges faced by students in developing countries like Nepal. It emphasizes the need for targeted interventions to enhance financial literacy and foster a more inclusive financial ecosystem.